2017
DOI: 10.1080/21623945.2017.1291102
|View full text |Cite
|
Sign up to set email alerts
|

Nck2, an unexpected regulator of adipogenesis

Abstract: The regulation of adipose tissue expansion by adipocyte hypertrophy and/or hyperplasia is the topic of extensive investigations given the potential differential contribution of the 2 processes to the development of numerous chronic diseases associated with obesity. We recently discovered that the loss-of-function of the Src homology domain-containing protein Nck2 in mice promotes adiposity accompanied with adipocyte hypertrophy and impaired function, and enhanced adipocyte differentiation in vitro. Moreover, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In this perspective, our studies on the role of Nck adaptor proteins in WAT development reveal that both Ncks regulate adipogenesis, but in an opposite manner and at different stages during this process. Nck2 is involved in regulating the transition of preadipocyte into adipocyte by regulating PERK activation and signaling ( Dusseault et al., 2016 , Haider et al., 2017 ), whereas our findings reveal that Nck1 controls preadipocyte commitment by modulating PDGFRα activation and signaling, and is required to maintain an adequate number of adipocyte precursor cells in WAT. Analysis of Nck1 and Nck2 interactome profiles in the preadipocyte and adipocyte might provide an understanding of how these two highly identical adaptor proteins differentially regulate WAT homeostasis.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In this perspective, our studies on the role of Nck adaptor proteins in WAT development reveal that both Ncks regulate adipogenesis, but in an opposite manner and at different stages during this process. Nck2 is involved in regulating the transition of preadipocyte into adipocyte by regulating PERK activation and signaling ( Dusseault et al., 2016 , Haider et al., 2017 ), whereas our findings reveal that Nck1 controls preadipocyte commitment by modulating PDGFRα activation and signaling, and is required to maintain an adequate number of adipocyte precursor cells in WAT. Analysis of Nck1 and Nck2 interactome profiles in the preadipocyte and adipocyte might provide an understanding of how these two highly identical adaptor proteins differentially regulate WAT homeostasis.…”
Section: Discussionmentioning
confidence: 72%
“…In this perspective, our work addressing the role of both Ncks in WAT unveils insights on mechanisms regulating adipogenesis. Indeed, we have previously demonstrated that Nck2 limits adiposity in mice and adipocyte differentiation in vitro ( Dusseault et al., 2016 , Haider et al., 2017 ). Mechanistically, we provided evidence that Nck2 regulates adipogenesis by controlling activation of PERK during preadipocyte to adipocyte transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGBS cells have been used to understand basic principles of adipogenesis, e.g., by comparing transcription factor usage in human and rodent cells [13], or by investigating the effect of radiation [15] or compressive force on human preadipocytes [16]. Using gain-and loss-of-function experiments, the effects of different [17][18][19][20] regulators of adipogenesis have been addressed. Recent literature demonstrates that microRNAs play a pivotal role in adipogenesis.…”
Section: Regulation Of Adipogenesismentioning
confidence: 99%
“…Although several nuclear receptors and transcription factors that regulate adipocyte differentiation and adipogenesis have been identified (Farmer, 2006), factors upstream to the activation of these transcription factors are still unknown. The activation of peroxisome proliferator-activated receptor γ (PPARγ) occurs in the intermediate or late stage of adipogenesis, and PPARγ activation has been determined to be a master regulator of adipogenesis (Haider et al, 2017). PPARγ has been linked to the transcription of genes expressed in mature adipocytes such as fatty acid binding protein (FABP4), required for transport of free fatty acids, and perilipin (PLIN1), which covers the surface of mature lipid droplets in adipocytes and regulates lipolysis.…”
Section: Introductionmentioning
confidence: 99%